Engineered 3D liver-tissue model with minispheroids formed by a bioprinting process supported with in situ electrical stimulation - WonJin Kim; GeunHyung Kim (Bioactive Materials, 2024)
Three-dimensional (3D) bioprinting, an effective technique for building cell-laden structures providing native extracellular matrix environments, presents challenges, including inadequate cellular interactions. To address these issues, cell spheroids offer a promising solution for improving their biological functions. Particularly, minispheroids with 50–100 μm diameters exhibit enhanced cellular maturation. We propose a one-step minispheroid-forming bioprinting process incorporating electrical stimulation (E-MS-printing). By stimulating the cells, minispheroids with controlled diameters were generated by manipulating the bioink viscosity and stimulation intensity. To validate its feasibility, E-MS-printing process was applied to fabricate an engineered liver model designed to mimic the hepatic lobule unit. E-MS-printing was employed to print the hepatocyte region, followed by bioprinting the central vein using a core-shell nozzle. The resulting constructs displayed native liver-mimetic structures containing minispheroids, which facilitated improved hepatic cell maturation, functional attributes, and vessel formation. Our results demonstrate a new potential 3D liver model that can replicate native liver tissues.